2000
DOI: 10.1037/h0087807
|View full text |Cite
|
Sign up to set email alerts
|

Ecological outcomes of adolescents in a psychoeducational residential treatment facility.

Abstract: Cross-sectional follow-up data on 111 adolescents in a re-education residential facility were obtained in three domains--school, legal, and level of care--at 6, 12, 18, and 24 months postdischarge. Reports by community-based professionals on individual functioning were assessed on several criteria, the most stringent of which indicated successful outcomes for nearly 60% of the adolescents. Characteristics of the more successful students are noted, applications of the psychoeducational residential approach for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 20 publications
2
57
2
1
Order By: Relevance
“…Successful graduates were also more likely to be engaged full time in some combination of work and school. In another study, a cross-sectional design using youth from one program found that the majority of youth performed satisfactorily in school after discharge: 94% at 6 months post discharge and 80% at 2 months and 24 months post discharge (Hooper, Murphy, Davaney, & Hultman, 2000).…”
mentioning
confidence: 99%
“…Successful graduates were also more likely to be engaged full time in some combination of work and school. In another study, a cross-sectional design using youth from one program found that the majority of youth performed satisfactorily in school after discharge: 94% at 6 months post discharge and 80% at 2 months and 24 months post discharge (Hooper, Murphy, Davaney, & Hultman, 2000).…”
mentioning
confidence: 99%
“…The definition of what constitutes residential treatment is further complicated by the range and variety of treatment models and philosophies currently in operation (Hooper et al, 2000). Bates et al (1997) noted that the efficacy of residential treatment is difficult to assess because of the utilization of different treatment modalities, making it difficult to compare different programs.…”
Section: Variations In Treatment Modelsmentioning
confidence: 99%
“…Yet the literature on the assessment of outcomes in adolescent residential treatment widely acknowledges the significant study design problems inherent in residential treatment outcome studies and the paucity of adequately designed studies (Chang et al, 996;Curry, 99;Curtis et al, 200;Gilliland-Mallo & Judd, 986;Goocher, 997;Gorske et al, 200;Hooper et al, 2000;Larzelere et al, 200;Mann-Feder, 996;Pfeiffer, 989;Pfeiffer & Strzelecki, 990;Swales & Kiehn, 995;Wilson et al, 98). These problems begin with a lack of consensus on what constitutes residential treatment (Bates et al,997;Curtis et al,200) and acknowledge that residential treatment outcome studies are inherently limited by the lack of appropriate comparison groups in the use of quasi-experimental designs (Curry,99).…”
Section: Problems In Study Designmentioning
confidence: 99%
See 2 more Smart Citations